2021
DOI: 10.3390/biomedicines9121921
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Therapy Resistance and Relapse in TNBC: Emerging Technologies to Target Breast Cancer-Associated Fibroblasts

Abstract: Breast cancer is the most diagnosed cancer and is the leading cause of cancer mortality in women. Triple-negative breast cancer (TNBC) is an aggressive form of breast cancer. Often, TNBC is not effectively treated due to the lack of specificity of conventional therapies and results in relapse and metastasis. Breast cancer-associated fibroblasts (BCAFs) are the predominant cells that reside in the tumor microenvironment (TME) and regulate tumorigenesis, progression and metastasis, and therapy resistance. BCAFs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 176 publications
(282 reference statements)
0
6
0
Order By: Relevance
“…CAFs are not targeted by paclitaxel, whereas bioactive PAs ( 1 )–( 4 ) maintain dose-dependent anti-proliferative effects presumably by blocking NFκB and HIF signaling and reducing tumor-promoting CAF activation. Because αSMA positive CAFs have been widely described as tumor-promoting and correlating with worse prognosis [ 44 , 110 ], we assume that mainly paracrine signaling enhances inflammation [ 37 ], i.e., NFκB, which might lead to increased vulnerability of co-culture spheroids to treatment with NFκB-inhibiting PAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAFs are not targeted by paclitaxel, whereas bioactive PAs ( 1 )–( 4 ) maintain dose-dependent anti-proliferative effects presumably by blocking NFκB and HIF signaling and reducing tumor-promoting CAF activation. Because αSMA positive CAFs have been widely described as tumor-promoting and correlating with worse prognosis [ 44 , 110 ], we assume that mainly paracrine signaling enhances inflammation [ 37 ], i.e., NFκB, which might lead to increased vulnerability of co-culture spheroids to treatment with NFκB-inhibiting PAs.…”
Section: Discussionmentioning
confidence: 99%
“…CAFs support tumor invasion and metastasis by enhanced secretion of extracellular matrix (ECM) components, mainly collagen, and proteases for ECM degradation [ 43 ]. Enhanced collagen type I acts as a physical barrier and correlates with reduced drug response [ 32 , 44 ]. Furthermore, a major role in tumor progression is attributed to the CAF-derived cytokines and growth factors that engage NFκB and HIF pathways [ 30 , 45 ], and correlate with cancer relapse and poor prognosis [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite diagnostic and therapeutic advances, breast cancer (BC) remains the most prevalent cancer worldwide and continues to account for a substantial number of tumorassociated deaths [1]. The progression of and prognosis for BC and other tumor entities is largely determined by the tumor microenvironment (TME) (i.e., by stromal cells including various immune cells and fibroblasts) [2][3][4]. Amongst the tumor-infiltrating immune cells, tumor-associated macrophages (TAM), predominantly derived from blood monocytes, play a crucial role.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the basal-like subtype of breast cancer, also known as triple-negative breast cancer (TNBC), shows the lowest survival rate and does not have effective treatments yet [ 3 , 4 ]. Recent studies reported that the TNBC subtype is much more difficult to treat than the other subtypes of breast cancer due to the lack of experimental data [ 5 , 6 , 7 ] and the interaction between CTL (cytotoxic T lymphocytes) and TNBC cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%